Lio de calendulas - Jules, Jacqueline, 1956-; Smith, Kim, 1986- (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2018)
Instead of the usual dusting Sofia volunteers to wash the car--but when she leaves the hose on her mother's marigolds get flooded and she calls on her sisters to save the situation.
Accelerated Reader AR
In Spanish.
Keywords: Hispanic American children -- Juvenile fiction; Hispanic American families -- Juvenile fiction; Chores -- Juvenile fiction; Sisters -- Juvenile fiction; Spanish language materials; Hermanas -- Novela juvenil; Ninos hispanoestadounidenses -- Novela juvenil; Familias hispanoestadounidenses -- Novela juvenil